tmem33 is essential for VEGF-mediated endothelial calcium oscillations and angiogenesis - Aaron M. Savage (Nature Portfolio, 2019)
Calcium signalling downstream of VEGF is essential for VEGF-induced angiogenesis. Here Savage et al. show that Transmembrane Protein 33 (TMEM33) is required for angiogenesis and the endothelial calcium response to VEGF, revealing a function for TMEM33 in multicellular organisms.